Student Management in Improving the Quality of Student Organizations - Nur Annisa Rahmawati; Nurul Latifatul Inayati (Yayasan Letiges Konsultan Sosial, 2023)
This study aims to describe student management in improving the quality of student organizations. This research uses a type of field research or field research with a phenomenological approach. Data collection techniques include observation, interviews, and documentation. Data sources in this study are primary data sources and secondary data sources. Data analysis is carried out through three lines of activities: data reduction, data presentation, and conclusions. Test the validity of the data, namely tricoagulation of sources, techniques, and time. The focus of this study is to describe student management in improving the quality of student organizations. The results showed that student management promotes the quality of student organizations, namely from the planning stage, namely forming HDI management, organizing, recruiting, and selecting HDI members, implementation, compiling work programs, and supervision by the school. The importance of coordination between all stakeholders, such as teachers, school staff, management, and parents to ensure student programs run according to plan.